The effect of organisational citizenship behaviours on Service Quality: a case of Midlands State University - Madzikanda, Godfrey M. (Midlands State University, 2017)
The study sought to examine the effects of organisational citizenship behaviour on service quality at MSU. Objectives of the study were to examine if altruism has any effect on responsiveness, to determine if conscientiousness has effect on reliability and to determine if sportsmanship has effect on empathy. A thorough review of literature of the two concepts of Organisational Citizenship Behaviour and Service Quality was conducted with a view to get a good insight of contributions of authorities on the two variables. Both exploratory and descriptive research approaches were used during the study. Questionnaires and interviews were used to gather information. A sample size of 360 students and 50 lecturers was used during the study. Both probability and non probability sampling was used. The questionnaire for lecturers sought to bring out information on their opinion about OCB while that of students sought to get their perception of service quality at MSU. In order to measure the responses interval data was arranged with the following descriptive being used strongly disagree: disagree: neither agrees nor disagrees: agree and strongly agree. The responses were weighted between 1 and 5 with one being the lowest and five the highest. Altruism, conscientiousness and sportsmanship are the OCB variables used in the study while reliability, responsiveness and empathy are the three service quality variables used in this study. The major findings were that altruism has an effect on responsiveness; conscientiousness has any effect on reliability while sportsmanship has an effect on empathy. The overall conclusion was that OCB has an effect on service quality. It was recommended that induction be done whenever a new member joins the institution and that lecturers are multi-skilled in their respective departments to enable them to cover for each other. It is also recommended that management consider including extra-role behaviours in annual appraisals to motivate employees and that team building initiatives be encouraged at the university.